2005
DOI: 10.1084/jem.20041896
|View full text |Cite
|
Sign up to set email alerts
|

VEGF-A induces tumor and sentinel lymph node lymphangiogenesis and promotes lymphatic metastasis

Abstract: The mechanisms of tumor metastasis to the sentinel lymph nodes are poorly understood. Vascular endothelial growth factor (VEGF)-A plays a principle role in tumor progression and angiogenesis; however, its role in tumor-associated lymphangiogenesis and lymphatic metastasis has remained unclear. We created transgenic mice that overexpress VEGF-A and green fluorescent protein specifically in the skin, and subjected them to a standard chemically-induced skin carcinogenesis regimen. We found that VEGF-A not only st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

36
586
4
9

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 644 publications
(640 citation statements)
references
References 36 publications
36
586
4
9
Order By: Relevance
“…Therefore, LN lymphangiogenesis, as LN angiogenesis, might contribute to the metastatic spread of breast cancer. In a transgenic mouse model of skin cancer, Hirakawa et al (2005) demonstrated that the induction of lymphangiogenesis by vascular endothelial growth factor A is involved in tumour progression. They furthermore showed that VEGF-A also induces lymphangiogenesis in the sentinel LN and that lymphangiogenesis is induced before metastasising (Hirakawa et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, LN lymphangiogenesis, as LN angiogenesis, might contribute to the metastatic spread of breast cancer. In a transgenic mouse model of skin cancer, Hirakawa et al (2005) demonstrated that the induction of lymphangiogenesis by vascular endothelial growth factor A is involved in tumour progression. They furthermore showed that VEGF-A also induces lymphangiogenesis in the sentinel LN and that lymphangiogenesis is induced before metastasising (Hirakawa et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In a transgenic mouse model of skin cancer, Hirakawa et al (2005) demonstrated that the induction of lymphangiogenesis by vascular endothelial growth factor A is involved in tumour progression. They furthermore showed that VEGF-A also induces lymphangiogenesis in the sentinel LN and that lymphangiogenesis is induced before metastasising (Hirakawa et al, 2005). Based on our data, it is difficult to investigate the mutual contribution of local and remote mechanisms to the induction of lymphangiogenesis in LNs of patient with breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…We have observed intratumoral lymphatic vessels and enlargement of peritumoral lymphatic vessels in VEGF-C-or VEGF-A-overexpressing squamous cell carcinomas. 43,82 Do intra-or peritumoral lymphatic vessels transport tumor cells? Controversy has prevailed on the presence and significance of intratumoral lymphatic vessels.…”
Section: The Role Of Vegfs In Lymphangiogenesismentioning
confidence: 99%
“…Tumor-secreted factors arrive in the sentinel lymph node through drainage of fluid and solutes from the periphery. These factors promote enlargement of the lymphatic networks inside the node, known as sinusoidal hyperplasia, 43,82 and possibly also affect blood vasculature in some models. 43,103 These changes have been suggested to 'prepare the soil' for successful metastasis at a later stage.…”
Section: The Role Of Vegfs In Lymphangiogenesismentioning
confidence: 99%
“…Furthermore, expression of these growth factors appears to correlate with lymph node metastasis in numerous common human cancers (for a review see Stacker et al, 2002a). Other protein growth factors that have also been implicated in tumour lymphangiogenesis are platelet-derived growth factors (PDGFs) (Cao et al, 2004) and VEGF-A (Hirakawa et al, 2005), however, the evidence for involvement of these molecules in tumour lymphangiogenesis is currently restricted to relatively few animal models and therefore requires analysis in a broader range of experimental models as well as extensive clinicopathological studies to correlate the expression of these molecules with metastasis in human cancer. In summary, the VEGF-C/VEGF-D/VEGFR-3 signalling system is currently the most attractive target for antilymphangiogenic therapeutics designed to restrict cancer metastasis, although it is likely that other validated targets will emerge in future.…”
mentioning
confidence: 99%